European banking regulation after the financial crisis: Franco-German conflict of interest during the negotiations on a single resolution fund - Tim Ferber (Freie Universität Berlin, Center for International Political Economy, 2016)
In response to the recent financial crisis, European policymakers put banking regulation in the Eurozone on top of the agenda. In 2016, as part of the newly created European banking union, a mechanism for resolving troubled banks, the Single Resolution Mechanism (SRM), became fully operational for the 19 member states of the euro area. The SRM was established to avoid future involvement of tax payers' money in the resolution of banks. This paper focuses on the negotiations on one of its instruments, the Single Resolution Fund (SRF), a fund of ex-ante contributions of Eurozone banks set up to winding down unviable banks. The SRF proved to be a main conflict issue during the negotiations. Germany and France were pushing for diverging preferences although both countries' banking sectors suffered from the crisis and both governments generally favored a regulatory approach on the European level. I provide an institutionalist explanation for these opposing positions of the two most important Eurozone countries. By drawing on the "Varieties of Capitalism" literature, I explain how the distinct features of these countries' financial and banking systems accounted for their preferences. On the one side, German negotiators sought to preserve the dominant way of bank-based corporate finance by particularly protecting savings and cooperative banks. On the other, the French government was in favor of higher contributions by the banking sector because market-based corporate finance is more prevalent in France. Nevertheless, France aimed at keeping its 'national champions' out as far as possible. This paper has important implications for how to think about preference formation in European financial regulation.
urn:nbn:de:101:1-201701125769
Keywords: 330